Epstein–Barr virus-mediated transformation of B cells induces global chromatin changes independent to the acquisition of proliferation. Issue 1 (3rd October 2013) - Hernando, Henar; Islam, Abul B. M. M. K.; Rodríguez-Ubreva, Javier; Forné, Ignasi; Ciudad, Laura; Imhof, Axel; Shannon-Lowe, Claire; Ballestar, Esteban
Abstract: Epstein–Barr virus (EBV) infects and transforms human primary B cells inducing indefinite proliferation. To investigate the potential participation of chromatin mechanisms during the EBV-mediated transformation of resting B cells we performed an analysis of global changes in histone modifications. We observed a remarkable decrease and redistribution of heterochromatin marks including H4K20me3, H3K27me3 and H3K9me3. Loss of H4K20me3 and H3K9me3 occurred at constitutive heterochromatin repeats. For H3K27me3 and H3K9me3, comparison of ChIP-seq data revealed a decrease in these marks in thousands of genes, including clusters of HOX and ZNF genes, respectively. Moreover, DNase-seq data comparison between resting and EBV-transformed B cells revealed increased endonuclease accessibility in thousands of genomic sites. We observed that both loss of H3K27me3 and increased accessibility are associated with transcriptional activation. These changes only occurred in B cells transformed with EBV and not in those stimulated to proliferate with CD40L/IL-4, despite their similarities in the cell pathways involved and proliferation rates. In fact, B cells infected with EBNA-2 deficient EBV, which have much lower proliferation rates, displayed similar decreases for heterochromatic histone marks. Our study describes a novel phenomenon related to transformation of B cells, and highlights its independence of the pure acquisition of proliferation.